2018
DOI: 10.1177/0743558418788402
|View full text |Cite
|
Sign up to set email alerts
|

“You Never Become Fully Independent”: Family Roles and Independence in First-Generation College Students

Abstract: First-generation (FG) college students often confront cultural mismatches between their interdependent backgrounds and university contexts that promote independent norms. Past work has documented this mismatch with various methodologies (e.g., self-report, lab experiments, longitudinal designs), but behavioral explorations have been minimal. Thus, the current study examined students' interdependent familial roles and the ways in which they enact either soft (e.g., self-expression) or hard (e.g., self-reliance)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(159 citation statements)
references
References 57 publications
9
141
0
9
Order By: Relevance
“…For many FGCS, the complexities of attending college begin when they forego prestigious universities’ offer of full scholarships to enroll in local community colleges or universities close to their families and communities (Perez & McDonough, ). By staying nearby, FGCS can continue to support their families while attending college (Covarrubias, Valle, Laiduc, & Azmitia, ). However, relative to FGCS who begin at 4‐year institutions, FGCS at community colleges have lower chances of transferring and completing 4‐year degrees (Cooper, ).…”
mentioning
confidence: 99%
“…For many FGCS, the complexities of attending college begin when they forego prestigious universities’ offer of full scholarships to enroll in local community colleges or universities close to their families and communities (Perez & McDonough, ). By staying nearby, FGCS can continue to support their families while attending college (Covarrubias, Valle, Laiduc, & Azmitia, ). However, relative to FGCS who begin at 4‐year institutions, FGCS at community colleges have lower chances of transferring and completing 4‐year degrees (Cooper, ).…”
mentioning
confidence: 99%
“…However, a few studies have suggested that family connections create more challenges for Latino students because their strong desire to continue fulfilling family obligations despite greater academic demands can present obstacles (e.g., Covarrubias, Valle, Laiduc et al, 2019;Espinoza, 2010). The extent to which closeness with parents contributes to Latino students' optimism for degree attainment is in need of further study.…”
Section: Connections With Others and Optimismmentioning
confidence: 99%
“…As Powles notes, the foundations of financial behaviour are laid in the early years [21]. Covarrubias et al considered the soft and hard forms of student independence [22]. Soft financial independence means significant support from the family, motivating students from such families to financial independence in order to acquire financial competencies.…”
Section: Analysis Of the Literaturementioning
confidence: 99%